The Phenomena of Transformation of Chemical Bond in Tungsten Wire Obtained by Radiation Technology - P. Chesnokov, boris; K. Abdrazakov, fyarid; V. Naumova, olga; V. Spiridonova, elena; V. Fedunina, tatiana (International Journal of Engineering and Technology, 2018)
The results of experimental studies in the field of radiation materials science, in particular, the phenomenon of chemical bond transformation in metal powders subjected to ionizing radiation in producing tungsten wire are presented. The phenomenon of energy conversion of an intracrystalline chemical bond between a material and a complex, including point defects and impurity atoms, leading to a change in the structure of sinter powder crystals, has been established experimentally.Â